Antioxidant Effectiveness and Phenolic Content of Saga Seed (Adenanthera pavonina) Extracts In Vitro Using DPPH and ABTS Methods - Yenni Yendriani; Djufri; Safrida S; Vivera Ruselli Puspa; Zumaidar (Jurnal Penelitian Pendidikan IPA, 2026)
Oxidative stress plays a crucial role in the development of various degenerative diseases, highlighting the need for safe and effective natural antioxidants. This study aimed to evaluate the antioxidant activity of saga seed (Adenanthera pavonina) extracts using DPPH and ABTS assays and to examine their relationship with total phenolic content (TPC). An in vitro experimental study with a quantitative approach was conducted. The extraction process was performed using maceration with 95% methanol and 95% ethanol as solvents. Antioxidant activity was determined based on IC₅₀ values, while TPC was analyzed using the Folin–Ciocalteu method and expressed as mg gallic acid equivalents (GAE)/g extract. The results demonstrated that the methanolic extract exhibited stronger antioxidant activity (IC₅₀ DPPH = 86.43 ppm; IC₅₀ ABTS = 54.07 ppm) compared to the ethanolic extract (IC₅₀ DPPH = 99.11 ppm; IC₅₀ ABTS = 72.41 ppm). The methanolic extract also showed a higher TPC value (319.90 mg GAE/g) than the ethanolic extract (194.33 mg GAE/g).